Highlighting of the interactions of MYD88 and NFKB1 SNPs in rats resistant to decompression sickness: toward an autoimmune response - Vallée, Nicolas; Dugrenot, Emmanuel; Desruelle, Anne-Virginie; Richard, Simone; Coupé, Stéphane; Ramdani, Céline; Guieu, Régis; Risso, Jean-Jacques; Gaillard, Sandrine; Guerrero, François (Frontiers in Physiology, 2023)
Decompression sickness (DCS) with neurological disorders includes an inappropriate inflammatory response which degenerates slowly, even after the disappearance of the bubbles. There is high inter-individual variability in terms of the occurrence of DCS that could have been mastered by the selection and then the breeding of DCS-resistant rats. We hypothesized the selection of single-nucleotide polymorphisms (SNPs) linked to autoimmunity operated upon a generation of a DCS-resistant strain of rats. We used the candidate gene approach and targeted SNPs linked to the signaling cascade that directly regulates inflammation of innate immunity transiting by the Toll-like receptors. Twenty candidate SNPs were investigated in 36 standard rats and 33 DCS-resistant rats. For the first time, we identify a diplotype (i.e., with matched haplotypes)—when coinherited—that strengthens protection against DCS, which is not strictly homozygous and suggests that a certain tolerance may be considered. We deduced an ideal haplotype of six variants from it (MyD88_50-T, _49-A, _97-C coupled to NFKB_85-T, _69-T, _45-T) linked to the resistant phenotype. Four among the six identified variants are located in pre- and/or post-transcriptional areas regulating MyD88 or NFKB1 expression. Because of missense mutations, the other two variants induce a structural change in the NFKB1 protein complex including one damage alteration according to the Missense3D algorithm. In addition to the MyD88/NFKB1 haplotype providing rats with a strong resistance to DCS, this also highlights the importance that the immune response, here linked to the genetic heritage, can have in the development of DCS and offer a new perspective for therapeutic strategies.